Stark-induced x-ray emission from H-like and He-like Rydberg ions - Gearba, M. A.; Komara, R. A.; Lundeen, S. R.; Fehrenbach, C. W.; DePaola, B. D. (My University, 2005)
The influence of small electric fields on the x-ray spectrum emitted by highly excited Rydberg ions formed in charge capture by bare and hydrogenic ions on Rydberg atoms is studied systematically. The branching ratio to direct decay to the 1S ground state of the H-like and He-like product ions is observed to saturate at electric fields which are on the order of 10V∕cm and which scale approximately as (Q∕n)5 where Q is the product ion’s core charge and n is the principal quantum number of the emitting levels. The limiting value of this branching ratio is sensitive to the degree of population alignment, and is found to be in good agreement with models that begin with classical trajectory Monte Carlo estimates of the alignment. The data indicate that multiple collisions with the Rydberg target are a significant factor and may alter the degree of alignment after the initial capture.